(untitled) (Research, Society and Development, 2022)
The medical mycology area presents a diagnostic and therapeutic challenge for healthcare professionals. Continuing education can develop important competencies for the appropriate diagnosis and treatment in the face of invasive fungal infections. The aim of the study was verify the perception of undergraduate healthcare students about a mycology focused extension course (in distance learning modality) during the COVID-19 pandemic as a complementary education. Application of an online query composed of 21 objective assumptions was performed. The answers followed the Likert scale, aiming to evaluate the quantitative and qualitative aspects of the course. The collected data were analyzed using descriptive statistics. After the conclusion of the course, the students agreed that they had their theoretical-practical knowledge expanded, increasing their confidence in facing the professional challenges that involve fungal infections. Students approved the course structure agreeing with the propositions with a high Average Ranking (RM) (between 4.58 and 5.00). In total, 88% of the students affirm that the topic "Fungal Infections" did not have the same level of approach in their graduate courses as in this extension course. When asked whether their performance and execution of the course would be better if it were carried out in a traditional way (i.e., not in a distance learning modality) heterogeneous scenario of evaluations was observed (RM=3.50). Mycology is an area that deserves attention within medical microbiology and the extension course can be an efficient alternative of a complementary strategy to make students better able to face the professional challenges related to fungal infections.